Use of steric encumbrance to develop conjugated nanoporous polymers for metal-free catalytic hydrogenation. Issue 80 (15th September 2016) - Tian, Chengcheng; Zhu, Xiang; Abney, Carter W.; Tian, Ziqi; Jiang, De-en; Han, Kee Sung; Mahurin, Shannon M.; Washton, Nancy M.; Dai, Sheng
Abstract : A novel approach to create conjugated nanoporous polymers with efficient hydrogenation activities toward unsaturated ketones was demonstrated. Abstract : The design and synthesis of metal-free heterogeneous catalysts for efficient hydrogenation remains a great challenge. Here we report a novel approach to create conjugated nanoporous polymers with efficient hydrogenation activities toward unsaturated ketones by leveraging the innate steric encumbrance. The steric bulk of the framework as well as the local sterics of the Lewis basic sites within the polymeric skeleton result in the generation of the putative catalyst. This approach opens up new possibilities for the development of innovative metal-free heterogeneous catalysts.